Respostas

2013-06-18T22:14:11-03:00

Olá, segue a resolução

 

x=(-\frac{1}{3})^{3}+[3^{-1}-(-3)^{-1}]^{-2} \\ x = (-\frac{1}{3})^3 + [\frac{1}{3} - (-\frac{1}{3})]^{-2}\\ x = (-\frac{1}{3})^3 + [\frac{1}{3} + \frac{1}{3}]^{-2}\\ x = (-\frac{1}{27}) + [ \frac{2}{3}]^{-2}\\ x = (-\frac{1}{27}) + [ \frac{3}{2}]^{2}\\ x = (-\frac{1}{27}) + [ \frac{9}{4}]\\ x = -\frac{4}{108} + \frac{243}{108} mmc\\ x = \frac{239}{108}

 

2) equações exponenciais:

 

81^{x-2}= \sqrt[4]{27}\\ 3^{4.(x-2)} = 27 ^{\frac{1}{4}}\\ 3^{4.(x-2)} = 3^{3.(\frac{1}{4})}\\ 4.(x-2) = 3.\frac{1}{4}\\ 4x - 8 = \frac{3}{4}\\ 16x - 32 = 3\\ 16x = 35 \\ x = \frac {35}{16}

 

5^{3x+1}=25 \\ 5^{3x+1}= 5^2 \\ 3x+1= 2 \\ 3x= 1 \\ x = \frac{1}{3}

 

 

 

1 5 1